Level of awareness of alzheimer’s disease among elderly people in Denpasar, Bali - Sabrina Annamma Philip; Desak Made Wihandani; Ni Nyoman Ayu Dewi (DiscoverSys Inc., 2020)
Background: Alzheimer’s disease (AD) is a chronic, irreversible, progressive, neurodegenerative that slowly impair memory and thinking skills especially in elderly people. This study aims to determine the level of awareness of AD among elderly people in Denpasar, Bali.Methods: A descriptive cross-sectional study was conducted by using self–administered validated questionnaire to determine the level of awareness of Alzheimer’s disease among the elderly people in Denpasar, Bali. The level of awareness could be classified into high awareness (>80%), moderate awareness (50-79%) and low awareness (<50%)Results: There were 50 subjects with 50 years old or above enrolled in this study. Most of the respondents had low awareness (82%) to the AD. About 38% of elderly people knew about AD and 58% of respondents said losing memory is a common thing in old age. Low education was said responsible increasing the risk of AD (30%). Only about 24% answered depression was prone to AD. In addition, about 34% said there was no cure for Alzheimer’s disease.Conclusion: Level of awareness among elderly people towards Alzheimer’s disease was low and needed improvement. Development and execution of educational programs should be carried out to the public to expand knowledge and understanding about Alzheimer’s disease.